Complementing and enhancing definitions of position tolerance for a real point based on ISO Geometrical Product Specifications (GPS). (August 2018) - Yan, Yiqing; Bohn, Martin; Peters, Steven; Heisel, Uwe
Abstract: According to ISO standards, the position tolerance symbol has only explicit definitions and examples of the specification for a derived point from a sphere under classification of a punctiform toleranced feature. For a real point on an integral surface, there are no explicit definitions and examples. Thus there are gaps in definition here causing undefined and irreproducible applications of position specifications into a real point. This paper suggests a new approach for explicitly defining the function-oriented position tolerance for real points, based on the analysis of its physical behaviour. As a result, an enhanced systematic approach for position tolerance is developed, which fills definition gaps.